Ecology and systematics studies of three amorphophallus species from Borneo - Angeline, Simon (Universiti Malaysia Sarawak, (UNIMAS), 2010)
Three selected Amorphophallus species that were A. borneensis (Engl. ) Engl. & Gehrm. from Kalimantan, A. hewittii Alderw. from Sarawak and A. lambii Mayo & Widjaja. from Sabah of Borneo were studied to determine the genetic relatedness based on both morphological and DNA fingerprinting. The three species studied have closed resemblance in their morphology characteristics and therefore two molecular markers were selected for the DNA fingerprinting which were the Direct Amplified Minisatellite Region (DAMD) using M 13 universal primer and the Random Amplified Polymorphic DNA (RAPD) using two OPD primers which were OPD 2 and OPD 2& The detail morphology characters for the three species were easily distinguished for the following characters which were the length of the peduncle, the spathe opening, base surface of inner spathe and the shape of stigma. However there were variation in the patterns and colours of both the leaf petiole and peduncle of the inflorescence within the species collected from different localities. Relationship between all of the species studied were determined by the Unweighted Pair-Group Method with Arithmetical Averages (UPGMA) analysed using the Ntsys-pc Numerical Taxonomy and Multivariate Analysis System Version 2.2 Exeter Software. Based on the data obtained three dendograms were generated. Both PCR-DAMD using M13 universal primer and PCR-RAPD using OPD 20 primer showed clear clustering into three groups separating each species according to the clusters. However PCR-RAPD using OPD 2 primer was able to differentiate the species but showed different relatedness compared to M13 universal primer and OPD 20 primer. Using the neighbour joining analysis, two dendograms were generated. The dendogram generated based on the PCR-DAMD using M13 universal primer and based on the PCR-RAPD using both OPD 2 and OPD 20 primer showed different relatedness among all three species studied.